Islamic Law and Social Media: Analyzing the Fatwa of Indonesian Ulama Council Regarding Interaction on Digital Platforms - Shuhufi, Muhammad; Fatmawati, Fatmawati; Qadaruddin, Muhammad; B, Jalaluddin; Muhammad Yunus, Muttaqien; M.Nur, Nainunis (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
The MUI fatwa serves as an answer to issues of Islamic law related to socio-religious issues in Indonesia. The fatwa comes through the ijtihad of the scholars so that it has legal authority so that Muslims have solutions to problems that arise. The article aims to examine Islamic law and social media which focuses on the MUI fatwa Number 24/2017 concerning guidelines for mu’āmalah and interacting using digital platforms. This research is sociological legal research that examines the function of law that works in social reality. Sociologically, the law functions as a tool to control and manipulate and change society for the better. The results of the study show that the MUI fatwa is a practical guideline for the use of social media, social interaction guidance, content verification guidelines, content creation, and content dissemination. So that ghibah, namīmah, intimidation, and hate speech will not occur. From the perspective of sociological law, the fatwa serves to provide guidance in social interaction so that society can be engineered and changed in a better direction. Thus, the fatwa as part of Islamic law is able to carry out its function as social control of society so that social media is used properly and usefully.